Characterization of the complete chloroplast genome of Chinese rose, Rosa chinensis (Rosaceae: Rosa). Issue 2 (3rd July 2019) - Lin, Wang; Huang, Jing; Xue, Meixiang; Wang, Xiumei; Wang, Chunhua
Abstract: Rosa chinensis known commonly as the Chinese rose, is a member of the genus Rosa native to Southwest China. In this study, the complete chloroplast genome of R. chinensis was sequenced and analyzed. Structural analysis of the complete chloroplast (cp) genome of R. chinensis that exhibits a typical quadripartite circular structure with 155, 097 bp in size, which contains a large single-copy region (LSC) of 85, 911 bp, a small single-copy region (SSC) of 17, 270 bp and a pair of inverted repeat (IR) regions of 25, 958 bp in each one. The cp genome of R. chinensis contains 130 genes, including 85 protein-coding genes, 37 tRNA genes and 8 rRNA genes. The phylogenetic Maximum-Likelihood (ML) analysis result shown that R. chinensis and Rosa odorata formed an independent clade with a 100% bootstrap support in phylogenetic relationship.